2013
DOI: 10.1128/jvi.02656-13
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic Network and Comparative Genomics Reveal a Diverged Member of the ϕKZ-Related Group, Marine Vibrio Phage ϕJM-2012

Abstract: bBacteriophages are the largest reservoir of genetic diversity. Here we describe the novel phage JM-2012. This natural isolate from marine Vibrio cyclitrophicus possesses very few gene contents relevant to other well-studied marine Vibrio phages. To better understand its evolutionary history, we built a mathematical model of pairwise relationships among 1,221 phage genomes, in which the genomes (nodes) are linked by edges representing the normalized number of shared orthologous protein families. This weighted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 83 publications
2
31
0
Order By: Relevance
“…Further searches showed that the 10 proteins encoded by these genes in SPN3US also have homologs in other recently identified ϕKZ-related phages, such as Vibrio phage JM2012 (25) and Erwinia phage Ea35-70 (46), and other giant phages (Table 6), supporting the broader relevance of utilizing a genetic system to study SPN3US. Examples of several proteins well conserved in all myoviruses (major head, sheath, and terminase proteins [47]) are also included in Table 6 to illustrate the intrinsically divergent nature of homologous proteins in these phages.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Further searches showed that the 10 proteins encoded by these genes in SPN3US also have homologs in other recently identified ϕKZ-related phages, such as Vibrio phage JM2012 (25) and Erwinia phage Ea35-70 (46), and other giant phages (Table 6), supporting the broader relevance of utilizing a genetic system to study SPN3US. Examples of several proteins well conserved in all myoviruses (major head, sheath, and terminase proteins [47]) are also included in Table 6 to illustrate the intrinsically divergent nature of homologous proteins in these phages.…”
Section: Discussionmentioning
confidence: 52%
“…Recent studies have demonstrated that extraordinarily large bacterial viruses (giant phages) are abundant in a variety of environments (9, 17, 24, 25, 35, 43). The ability to define such giant phages at the genome level has been limited due to the fact that a large proportion of their proteins have not been characterized.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacillus phages 0305phi8-36Figure 3A and Table S5) can support evolutionary links between jumbo phages and smaller-genome phages (Hendrix, 2009;Adriaenssens et al, 2012;Jang et al, 2013). Together, the visualization and analysis of gene content relationships of the jumbo phages as a network revealed the global distribution of genetically diverse groups of jumbo phages across 2,259 viruses, in which most of them together with smaller-genome phage(s) are placed into two major groups comprising viruses belonging to the Tevenvirinae as well as the Phikzvirus/Elvirus/Agrican357virus/Rsl2virus, respectively, and others form evolutionary distinct clades (Gill et al, 2012;Yamada et al, 2010) (Table S5).…”
Section: Transcriptome and Proteome-based Functional Annotationsmentioning
confidence: 96%